The The Effect of GaAlAs Laser, Sandblasting, and Primers on Bond Strength between Zirconia Ceramic and Direct Resin Composite after Thermocycling: Bonding zirconia ceramic with resin composite - Kukiattrakoon, Boonlert; Kosago, Pitchaporn (Brazilian Dental Science, 2021)
Objective: This study was conducted to evaluate the shear bond strength (SBS) of resin composite on zirconia ceramic after different surface treatments and thermocycling. Material and Methods: Two hundred and seven zirconia specimens were divided into 9 groups and treated as follows: Group C-no treatment (served as the control); Group PC-Clearfil Ceramic primer (CP); Group PZ-Z-Prime Plus primer (ZP); Group A-sandblasted with 50 µm Al2O3 at 0.25 MPa for 20 s at a distance of 10 mm; Group AC-sandblasted and coated with CP; Group AZ-sandblasted and coated with ZP; Group L-GaAlAs diode laser with 808±5 mm wavelength, 3 watts power, and 10 Hz frequency; Group LC-GaAlAs diode laser coated with CP; and Group LZ-GaAlAs diode laser coated with ZP. All specimens were directly bonded with a resin composite cylinder using Adper Scotchbond Multi-purpose. Specimens were stored at 37ºC for 30 days and subjected to 2,500 thermocycles from 5ºC and 55ºC before the SBS was performed. One-way ANOVA and Tukey’s HSD test (=0.05) were performed. Surface topography changes were evaluated with a scanning electron microscope (SEM). Results: Sandblasting combined with CP or ZP (25.08±0.86 and 24.78±0.13 MPa, respectively) yielded the highest SBS and was significantly different from other methods (p<0.05). SEM showed various degrees of changes depending on different surface treatments. Conclusion: Surface treatment by sandblasting combined with a CP or ZP significantly provide the highest SBS between zirconia and resin composite. KEYWORDS Bond strength; Resin composite; Surface treatment; Zirconia ceramic.